Improving Cultural Competence via a Virtual Clinic for Service Providers in Rural Eastern North Carolina - Powers, Savannah E (East Carolina University, 2017)
The Latino population in the United States of America is the nation’s largest ethnic minority, and is steadily increasing in size and diversity. The Southeastern region leads the US in Latino population growth (Pew Research Center, 2016) and North Carolina’s (NC) Latino population increased by 111% between 2000 and 2010 (Trippett, 2014). Such an increase in a minority population poses significant challenges in providing culturally competent patient care. The Aging Latino Research Team (ALRT), a community-university partnership between the Eastern Carolina Council Area Agency on Aging (AAA) and East Carolina University, conducted a study to establish linkages with the Latino community and their health service providers to describe the health and social needs of aging Latinos in eastern North Carolina. Cultural insensitivity was identified during interviews with key informants as well as focus groups with older adult Latinos. There is limited information about the use of virtual clinic/virtual simulation to facilitate cultural competency training, although it has previously been used in provider-client technical skill training. The purpose was to improve cultural competence among service providers in eastern North Carolina. This program evaluation involved three stages. First, a literature review on virtual clinics and cultural competence was conducted. Next, five experts in virtual clinic/simulation were interviewed for their perspectives on design and effectiveness. Finally, the availability of Canopy, a National Institutes of Health (NIH) sponsored online medical Spanish language program was investigated.
Keywords: cultural competence; Latino; virtual clinic; virtual reality; nursing